RIGHT TO PROPERTY: THE LAND ACQUISITION ACT 1960 AND THE SHARIAH PERSPECTIVE - Nor Asiah Mohamad; Azlinor Sufian; Azmi Harun; Naemah Amin (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2013)
Islamic law recognizes both private and community property. This community rights are manifested in forms of entitlement for charitable purposes, known as waqf or trusts, sadaqah as well as zakat. Under the Sha‘riah, however, ownership of all property ultimately rests with God. Though individual property rights are upheld, there is a corresponding obligation to share, particularly with those in need. In Malaysia, the right to property is a constitutional right and thus, the acquiring authority cannot deprive a person of his land in an arbitrary manner. This paper discusses the extent of which the acquisition law falls in line with Shari‘ah thus preserving the right to property as determined by Shari‘ah to individuals. Similarly, the paper also looks at some basic principles sustained by the court in determining whether the working of the acquisition law falls within the constitutional guarantee provided under Article 13 of the Federal Constitution and the Sha‘riah. A study of the case law reveals that human errors due to greediness and lack of responsibility have contributed to some of the problems in land acquisition.